META-ANALYSIS OF STUDENT'S MISCONCEPTIONS FOR BIOLOGICAL MATERIALS FOR SCIENCES CLASS SMA/MA - Rahma Yeni; Z Zulyusri (Jurnal Pelita Pendidikan, 2021)
Misconceptions result in poor student learning outcomes and become an obstacle in the other learning process. It is necessary to know exactly where the students' misconceptions lie. This type of research is a meta-analysis by collecting, analyzing, and summarizing the results of relevant research in the form of articles that have been previously researched. Of the six research results regarding misconceptions in Biology students of class XII IPA analyzed, it is inseparable from students' misconceptions that are quite varied. The catabolism sub material that experienced the largest and smallest student misconceptions, respectively, was the indicator identifying each step that occurred in cellular respiration and the indicator determining the ratio of fermentation and aerobic respiration. Catabolism contained quite complicated stages with complex terms. To be remembered and understood by students who can trigger misconceptions. The higher the percentage of students' misconceptions, the lower students' understanding of the concepts in the material. Overall, students' misconceptions are caused by internal factors (students themselves) and external factors such as teachers, textbooks, and the context of the material being studied. Further action is needed on the part of teachers and related organizations to ensure efforts are made to reduce misconceptions among students.